Case report: Isolated tubular basement membrane deposits in a patient with systemic lupus erythematosus - A diagnostic challenge - Gomes, Orlando Vieira; Santana, Leonardo Fernandes e; Duarte, Rita Marina Soares de Castro; Rodrigues, Mateus de Sousa; Nicacio, Jandir Mendonça; Brito, Dyego José de Araújo; Muniz, Monique Pereira Rêgo; Salgado-Filho, Natalino; Neves, Precil Diego Miranda de Menezes; Silva, Gyl Eanes Barros (Frontiers in Medicine, 2022)
Lupus nephritis is one of the most serious and frequent manifestations of systemic lupus erythematosus. It usually presents in the first years of the disease, which suspicion should be raised in cases of elevated serum creatinine, presence of proteinuria above 500 mg/day or active urinary sediment, in the absence of other apparent causes such as urinary tract infection and use of nephrotoxic drugs. In most cases, it affects the glomerulus, and its presentation is rare in the form of isolated tubulo-interstitial disease. In this report, we describe a case of lupus nephritis diagnosed after 2 years of illness, in the form of atypical isolated tubular disease, characterized by massive deposits in the tubular basement membrane. Clinically, there were altered renal function, subnephrotic proteinuria, and evolution to a complete clinical response after immunosuppressive treatment.